The Anthropology of Secularity beyond Secularism - Lebner, Ashley B. (2015)
This article begins by exploring why secular studies may be stagnating in anthropology. Contrary to recent arguments, I maintain that rather than widening the definition of secularism to address this, we should shift our focus, if only slightly. While secularism remains a worthy object, foregrounding it risks tying the field to issues of governance. I therefore suggest avoiding language that privileges it. Moreover, in returning to Talal Asad's "secular", it becomes evident that care should be taken with the notion of "secularism" to begin with, even if he did not emphasize this analytically. Conceiving of secularism as a transcendent political power, as Asad does, is not only a critique of a secularist narrative, but also a secularist truism itself that can potentially cloud ethnography if applied too readily. A way forward lies in carefully attending to secular concepts, as Asad suggests, and in exploring a version of secularity inspired by the work of Charles Taylor.
Keywords: Charles Taylor; Ethnography; Modernity; Secular; Secularism; Secularity; Talal Asad